Kemandirian Belajar Siswa dalam Pembelajaran Daring Berbantuan E-Modul Berbasis STEM (Science, Technology, Engineering, and Mathematics) Ditinjau dari Hasil Belajar Kognitif - Izza, Lailatul; Hartono, Hartono (UPEJ Unnes Physics Education Journal, 2021)
The spread of the Covid-19 pandemic in Indonesia has caused the learning process to be carried out from home and students are required to be able to carry out the learning process independently. Based on these problems, teaching materials are needed that can help students learn independently, one of them is by using e-modules based STEM. This study aims to analyze differences in student learning outcomes in online learning assisted by e-modules based STEM and online learning assisted by modules from schools dan analyze differences in student learning independence in online learning assisted by e-modules based STEM in terms of cognitive learning outcomes. The research was conducted at SMA Negeri 2 Demak. This research is an experimental research with Nonequivalent control group design. The subjects in this study were students of class XI MIPA 1 and XI MIPA 2. Data collection methods used were documentation, questionnaires and tests. The data analysis technique used includes normality test, homogeneity test, one way ANOVA test and t test. Based on the results of the study, it shows that there are differences in student learning outcomes in online learning assisted by e-modules based STEM and online learning assisted by modules from schools and there are differences in student learning independences in online learning assisted by e-modules based on STEM in terms of cognitive learning outcomes.